Digital transformation of planning in the pharmaceutical sector - Santos Hernandez, Andrés Felipe; Jimenez Tocasuche, Ana María; Durán Sanjuán, María Fernanda; Colorado Gonzalez, Angie Jimena; Carrillo Barreto, Ingrid Yohana (My University, 2022)
Purpose: To adjust the inventory supply planning, through digital transformation that allows automation and tracking of demand behavior in real time and with low cost tool. Methodology: The collected database is loaded into an Excel along with the required input variables in each of the inventory policies. The data is processed and imported into Python, the demand forecasting is made and the policies are simulated to choose the one that generates the lowest cost. Results: The algorithm indicates the inventory scheduling to be implemented by the company according to the policy that allows the lowest costs and that supplies the demand of each product. Originality: The design of an original tool, that allows obtaining accuracy of the inventory management, with easy interaction of the user and the algorithm, through the reception of information and output of results in Excel, processed by python, across the synergy between the two programs.

Propósito: Ajustar la planificación del abastecimiento del inventario, a través de la transformación digital que permita la automatización y seguimiento del comportamiento de la demanda en tiempo real y con una herramienta de bajo costo. Metodología: La base de datos recopilada se carga en un Excel junto con las variables de entrada requeridas en cada una de las políticas de inventario. Los datos son procesados ​​e importados a Python, se realiza el pronóstico de demanda y se simulan las políticas para elegir la que genera el menor costo. Resultados: El algoritmo indica la programación de inventarios a implementar por la empresa de acuerdo a la política que permita los menores costos y que supla la demanda de cada producto. Originalidad: El diseño de una herramienta original, que permita obtener precisión en la gestión del inventario, con fácil interacción del usuario y el algoritmo, a través de la recepción de información y salida de resultados en Excel, procesados ​​por python, a través de la sinergia entre ambos programas.
Keywords: Transformación digital; Innovaciones tecnológicas; Algoritmos computacionales; Programación - Inventarios; Transformación digital; Transformación digital; Innovaciones tecnológicas; Innovaciones Tecnologicas; Transformación digital; Algoritmos computacionales; Algoritmos computacionales; Programación - Inventarios; Programación - Inventarios